Analisis Keekonomian pada Produksi Lapangan “RF” Menggunakan Skema Production Sharing Contract (PSC) Cost Recovery - Krisdayanti, Ni Ketut; Adawiyah, Fathul; Sinurat, Daniel (Jurnal Offshore: Oil, Production Facilities and Renewable Energy, 2025)
Reserve estimation and economic analysis are essential components in oil and gas field development to determine production feasibility. This study aims to evaluate production reserves and economic performance of the “RF” Field in the “R27” and “A10” reservoirs using the Production Sharing Contract (PSC) Cost Recovery scheme. Reserve estimation and production forecasting were conducted using Decline Curve Analysis (DCA) through MBAL software, while the economic evaluation was performed using Microsoft Excel based on the PSC Cost Recovery fiscal parameters. This study also examines factors influencing economic value and projects future cumulative production under two development scenarios. The results indicate cumulative production of 75.3255 MMSCF for the “R27” reservoir and 89.3819 MMSCF for the “A10” reservoir. The economic analysis shows a Net Present Value (NPV) of 5,276.97 MUSD and an Internal Rate of Return (IRR) of 1665.13%, with a Pay Out Time (POT) of one year. These results indicate that the development of the “RF” Field is economically feasible and suitable for continued production